2017
DOI: 10.1038/s41598-017-18258-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfined water can orient and cause long-range dipolar interactions with biomolecules

Abstract: Surface properties are generally determined by the top most surface layer also defining how molecules adsorb onto it. By exploring effects due to interactions with deeper subsurface layers, however, long-range interaction forces were found to also significantly contribute to molecular adsorption, in which hydration of the subsurface region is the key factor. Water molecules confined to a subsurface amphiphilic gradient are confirmed to cause these long-range dipolar interactions by preferential orientation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In the absence of a dipole field, and if the intermolecular distance is below 5 Å, water molecules can organize themselves into a tetrahedral network due to hydrogen-bond interactions. 3 In crystalline ice, a welldefined tetrahedral network appears, while in bulk water, only a short-range order remains. 48 Also, from the analysis of the water−water angle distribution, water molecules in the vicinity of hydrophobic surfaces were shown to exhibit a higher order than in the bulk.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a dipole field, and if the intermolecular distance is below 5 Å, water molecules can organize themselves into a tetrahedral network due to hydrogen-bond interactions. 3 In crystalline ice, a welldefined tetrahedral network appears, while in bulk water, only a short-range order remains. 48 Also, from the analysis of the water−water angle distribution, water molecules in the vicinity of hydrophobic surfaces were shown to exhibit a higher order than in the bulk.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This gradient is at the origin of long-range dipolar interactions governing the protein interactions with the surface. 3 Other examples show that the hydration layer plays a decisive role in the adsorption of peptides, 4 proteins, 5 DNA, 6 or RNA. 7 Owing to the crucial role of the hydration layer, several authors have focused on understanding the effect of surface chemistry, and of the surface structure, on the hydration layer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Elsewhere, in vitro multiple protein adsorption tests demonstrated that the pre‐adsorbed albumin on siloxane surface could not be displaced by fibrinogen or immunoglobulin because of the small size and tenacious binding of albumins to siloxane surfaces . Recent studies albumin binding to hydration stratified pp matrix (50 nm of a silica‐like hydrophilic base layer with the dosed addition of O 2 gas, followed by a hydrophobic cover layer of HMDSO pp of varying thickness) have shown that nano‐confined hydration of the deeper silica‐like sub‐surface layers also influenced the albumin adsorption and related conformation …”
Section: Siloxane Plasma Polymersmentioning
confidence: 99%
“…[ 30,32,33 ] Recently, nm‐thick HMDSO‐derived PPFs have been applied as surface chemistry‐defining cover layers to gain new insights into protein and bacteria adhesion. [ 34,35 ] Noteworthy, water intrusion was found to affect biomolecule adsorption, whereas the mechanical properties of the substrate material appeared to be of less importance. Furthermore, HMDSO plasma‐modified hydrogels allow for the controlled release of drugs.…”
Section: Introductionmentioning
confidence: 99%